Arterial Stiffness and Anti-Tumor Necrosis Factor-Alpha Therapy in Ankylosing Spondylitis: Results With Long-Term Two Year-Follow-Up - Murat KARKUCAK; Erhan ÇAPKIN; Abdulkadir KİRİŞ and Mürsel ŞAHİN and Ayşegül KÜÇÜKALİ TÜRKYILMAZ and; KARACA and; at GÖKMEN and; t AYAR (Archives of Rheumatology, 2014)
Objectives: This prospective clinical study aims to evaluate the effectiveness of long-term of anti-tumor necrosis factor-alpha (TNF-a) therapy on arterial stiffness in ankylosing spondylitis. Patients and methods: A total of 28 active ankylosing spondylitis patients (21 males, 7 females; mean age 33.5±9.5 years; range 20 to 52 years) were enrolled. Patients’ values for before the initiation of biological therapy and mid-term (24 weeks) evaluation were reported. For further evaluation, this initially reported patients were contacted two years after anti-TNF-α therapy, and their arterial stiffness was assessed by using pulse wave velocity. Results: After two years of anti-TNF-α therapy, despite the significant improvements in patients’ symptoms and clinical activity parameters including Bath Ankylosing Spondylitis Disease Activity Index score (4.9±0.9, 1.9±0.5 and 1.8±0.9, p=0.0001), erythrocyte sedimentation rate (35.5±23.1 mm/h, 13.8±9.2 mm/h and 25.0±17.9 mm/h, p=0.0001), and C-reactive protein (2.1±1.6 ng/dl, 0.4±0.3 ng/dl and 0.6±0.9 ng/dl p=0.0001), no significant difference was observed in arterial stiffness parameters (7.9±1.3 meter/second, 7.7±1.3 meter/second and 8.3±1.1 meter/second, p=0.620). Conclusion: In line with the previous 24-week evaluation, the results at two-year follow-up indicates that anti-TNF-α therapy does not improve arterial stiffness in patients with ankylosing spondylitis.